2013
DOI: 10.1097/01.nurse.0000428709.81378.7c
|View full text |Cite
|
Sign up to set email alerts
|

Does an oral care protocol reduce VAP in patients with a tracheostomy?

Abstract: Tooth brushing with toothpaste and applying CHG 0.12% solution may be an effective oral care protocol to reduce the VAP rate in patients in PCUs with tracheostomies who are being mechanically ventilated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
5
0
5
Order By: Relevance
“…5 This highlights the importance of oral hygiene protocols in ICU environments. 2,5,10 In this context, a recent study 19 highlighted the importance of brushing with toothpaste and applying chlorhexidine 0.12% solution; this protocol may represent an effective method to reduce associated pneumonia among patients with mechanical ventilation and tracheostomies.…”
Section: Discussionmentioning
confidence: 99%
“…5 This highlights the importance of oral hygiene protocols in ICU environments. 2,5,10 In this context, a recent study 19 highlighted the importance of brushing with toothpaste and applying chlorhexidine 0.12% solution; this protocol may represent an effective method to reduce associated pneumonia among patients with mechanical ventilation and tracheostomies.…”
Section: Discussionmentioning
confidence: 99%
“…Critical care nurses play a crucial role in maintaining and assessing oral health among invasively ventilated, critically ill patients. Comprehensive oral care, using either chlorhexidine oral rinse or gel and toothbrush, together with preventing microaspiration of oropharyngeal secretions may reduce the risk of developing ventilator‐associated pneumonia (VAP) in these patients (AACN Practice Alert, ; Conley et al , ; Hillier et al , ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 9 , 20 - 22 The recommended frequency of performing oral care also varies: every 2 hours, 4 hours, 8 hours or 12 hours. 9 , 13 , 19 , 23 - 25 The literature did not confirm which was better for reducing the risk of VAP. Various surveys of ICUs found in the literature from the USA, Europe and the UK concluded that evidence-based oral care practices could reduce the incidence of VAP in patients.…”
mentioning
confidence: 96%